UPACARA ADAT SEREN TAUN CIPTAGELAR SEBAGAI DAYA TARIK WISATA BUDAYADI KABUPATEN SUKABUMI - Umu Kulsum, - (2009)
The Title of this examination is "Upacara Adat Seren Taun Ciptagelar sebagai Daya Tarik Wisata Budaya di Kabupaten Sukabumi." The background of this examination by the interesting of writer about the lesson is upacara adat seren taun (seren taun ceremony) in kasepuhan Ciptagelar. The seren taun ceremony has a something special within a culture history, and also a combined of the agenda which presented a traditional science of art by kasepuhan peoples and an illustration about a circle life of kasepuhan eoples. The existence of kasepuhan Ciptagelar as sesepuh lembur (oldest village) of 568 a little villages on 360 a big villages being an uniquely of another special things. The aim of seren taun ceremony as a thanksgiving to Dewi Sri and God for the harvest rice. Seren taun is part of the culture element which is has value for the agraris peoples (live with paddy agricultures). Seren taun is been an interest of culture tourism interest. This examination is to maximize a seren taun ceremony and every element inside it as a culture tourism interest and to steal an attention of government and stakeholders. Which is the advantages is to optimal a seren taun ceremony, so it can give a feedback. Any data and information about seren taun is get from observation and interview. The method is use a descriptive qualitative, with etnografi and SWOT/TOWS analysis. It's been a validity test for a process and data. The etnografi analysis is used to approximation of a culture, and SWOT/TOWS is used to tourism approximation. By an illustration how a relationships between cultures and tourism and also a subject inside, so the potency can used maximize as culture interest tourism. Hope it will make a holistic of tourism and a sustainable of tourism. So, a mindset about the indigenous of purpose the cultures, hope it can be change. Otherwise, it can be an identity, and something it could develop by tourism activity.